Preservation of Papua’s Local Food through Frozen Sagu Sep Innovation and Multichannel Marketing Strategy - Longgy, Dodhy Hyronimus Ama; Tini Adiatma; Cici Girik Allo; Fety Rochyawaty Qudrat Mulya (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was conducted in South Papua, focusing on the empowerment of the “Mama Juan” MSME, a local producer of the traditional food Sagu Sep. The program addressed key challenges such as limited product shelf life, manual financial management, and restricted marketing reach. The method used was Participatory Action Research (PAR), which encompassed socialization, training and technology implementation. The introduction of freezers, ovens, coconut graters, and vacuum sealers enabled the production of Frozen Sagu Sep with improved hygiene, durability, and market value. Financial management was strengthened through QRIS and simple accounting applications, while digital marketing and rebranding expanded market reach and visibility. The results show a significant transformation toward modern, technology-based business practices, providing a replicable empowerment model for local MSMEs in Southern Papua.